PERANCANGAN USER INTERFACE DAN USER EXPERIENCE PADA APLIKASI VISITING KOTA METRO - Wulandari, Ika Arthalia; Pujianto, Pujianto (Universitas Muhammadiyah Metro, 2023)
Metro City has diverse tourism potential with its natural, artistic, and cultural wealth, so tourist destinations and culinary places in Metro City are growing in quality and quantity. However, due to the lack of information about tourist places, the number of visitors to tourist destinations and culinary places does not increase significantly, so people must look for a single unit of information for each tourist and culinary destination. So we need information media to facilitate problem-solving in the form of tourist destination applications and culinary places for tourists. With this application, it is hoped to help the problems of tourists who have difficulty finding information about tourist destinations and culinary places in Metro City. The application is designed using the User Centered Design method. Based on the results of testing the level of user satisfaction, the design of the Metro City Visiting application is included in a perfect interval with an average proportion of 80% so that the design can be continued to the application development stage.